Analysis of Interest, Strategy, Model in Learning Angklung for Children Aged 5-6 Years - Izzati, Khoerul; Pamungkas, Joko (Electronic Journal of Education, Social Economics and Technology, 2024)
Early Childhood Education emphasizes the importance of learning art through play. There are various arts in the environment, including: dance, music, fine arts, drama, and literature. Music can be one way for children to express their feelings and show their emotions. This study will analyze the interests, strategies and also learning models of one of the musical arts in kindergarten, namely Angklung. In most kindergartens, angklung has become part of art learning because of the importance of preserving traditional music art culture from an early age. This study uses a qualitative method with a descriptive approach. Data were collected from observations, interviews with teachers and principals, and documentation. The results showed that there were differences in children's interests in learning angklung, which were based on the strategies and learning models applied by the teacher. Playing the angklung has a very good impact on children, including: children can adjust the tempo, differentiate the tone and rhythm of the song.